delta-L-(alpha-aminoadipoyl)-L-cysteinyl-D-valine synthetase: the order of peptide bond formation and timing of the epimerisation reaction. - Shiau, C; Baldwin, J; Byford, M; Sobey, W; Schofield, C (1995)
delta-L-(alpha-Aminoadipoyl)-L-cysteinyl-D-valine (ACV) synthetase catalyses the formation of the common precursor tripeptide of both the penicillin and cephalosporin antibiotics from the L-enantiomers of its constituent amino acids. Replacement of cysteine with L-O-methylserine in preparative-scale incubations led to the isolation of both L-O-methylserinyl-L-valine and L-O-methylserinyl-D-valine dipeptides. The dipeptides were characterized with the aid of authentic synthetic standards by both 1H NMR and electrospray ionization MS. A revised mechanism for ACV biosynthesis involving formation of the cysteinyl-valine peptide bond before the epimerisation of valine and subsequent condensation with the delta-carboxyl of L-alpha-aminoadipate is therefore proposed.